Analysis of Key Factors Affecting Risk Tolerance in Project-Oriented Firms Using Hybrid Fuzzy DEMATEL-ISM: An Empirical Study - Khalilzadeh, Mohammad; Božanić, Darko; Puška, Adis (Yugoslav Journal of Operations Research; Vol 35 No 3 (2025), 2025)
Project risk management is one of the project management knowledge areas that identifies, analyzes and deals with project risks. One of the important factors influencing the decision-making of a project-based organization is the level of risk tolerance of organization. This study focuses on the factors affecting the level of risk tolerance of project-based organizations. For this purpose, in the first step, the potential factors affecting risk tolerance are extracted by reviewing the related literature. In the next step, the factors affecting the organization's risk tolerance level are identified by using the Fuzzy Delphi method in several steps. The most effective factors are identified by experts’ judgment using a questionnaire. Then, the relationships between these factors are determined by using the Interpretive Structural Modeling (ISM) method. The intensity of these relationships and the intensity of the effect of the factors are investigated by using the Fuzzy DEMATEL method. Finally, the factors are ranked based on their weights by utilizing the Fuzzy DEMATEL method. In this study, 13 external and internal factors are ranked using questionnaires based on the experts’ opinions. Four external factors include political conditions and international relations, the conditions of the capital markets such as stock market, investment security and government support. These factors have significant influence on the other factors as well as the project-based organization. The findings of this study direct project managers to accurately identify the  risk tolerance level of the key project stakeholders in order to efficiently plan and implement project risk management and achieve project goals.